Combining ability analysis for seed yield and its components in Indian mustard (Brassica juncea L) - Ajay Pal Yadav; Gaibriyal M Lal; Vaidhurya Partap Sahi (Journal of Oilseed Brassica, 2026)
Ten diverse lines of Indian mustard (Brassica juncea L.) genotypes were crossed in diallel mating design excludingreciprocals to study combining ability. The mean squares due to genotypes including parents, crosses and parents vs.crosses were significant for seed yield/ plant, days to 50% flowering, days to maturity, main raceme length, siliquae onmain raceme, siliquae per plant, siliqua length, seeds per siliqua, harvest index. The analysis of variance revealedsignificant mean sum of squares of general combining ability (GCA) and specific combining ability (SCA) for all thecharacters. The estimates of GCA effects revealed that parents, viz. NRCDR-02, RH-749, RH-761 and Brijraj weregood general combiners for yield contributing traits. The best specific cross combinations for yield and its attributingtraits were crosses DRMR IJ-31 × Pusa Bold, DRMR 150-35 × RH-761, DRMR 150-35 × Brijraj, DRMR 150-35 ×RH-406, Pusa Bold × JM-2, NRCDR-02 × RH-761, DRMR 1165-40 × Brijraj on the basis of pooled analysis. These F s 1may be exploited for obtaining transgressive segregants for development of hybrid varieties in Indian mustard